The structure of anionic NbHn− (n = 2–15) clusters and their maximum hydrogen capacity. (1st April 2022) - Liao, Y H; Zhou, W L; Lyon, J T; Peng, F; Lu, C
Abstract: The geometrical structures of the lowest energy states of anionic niobium-doped hydrogen clusters are determined based on Crystal structure AnaLYsis by the Particle Swarm Optimization (CALYPSO) isomer search method. The geometries and relative stabilities are determined by the B3LYP hybrid density functional theory (DFT) method. The calculated results show that a niobium atom can absorb up to twelve hydrogen atoms in the anionic clusters. In exploring the stability, electronic properties, and photoelectron spectra of NbH n − clusters, the NbH12 − cluster is found to possesses a relatively high binding energy, high second-order differential energy, and a large HOMO–LUMO gap. The hydrogen storage density of the NbH12 − cluster is calculated as 11.5 wt%. The present findings enrich the database of transition metal doped hydrogen clusters and the insights are important in the pursuit of efficient hydrogen energy storage materials.